Tauhid Education in the Family Towards the Benefit of the Household (Analysis of Qs. Al-Baqarah Verse 132) - Imam Arifin; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2024)
The focus of education that will be studied is how the concept of monotheism education in Islam according to the Al-Qur'an Surah Al-Baqarah Verse 132 is a process of guiding humans to remain firm in their belief that Allah is Almighty and only submits to Him until the end of life. The relevance of monotheism education in families today is that monotheism education must try harder to continue paying attention by creating varied methods.